PARE0014 Exploring the added value of a booster session after completing the dutch self-management training "challenging arthritis". (15th June 2017) - Vos, M; Brink, R Van den; Jong, S de; Ammerlaan, J
Abstract : Background: In the Netherlands, the peer-guided self-management training "Challenging Arthritis" exists for over 15 years and is being organized by the Dutch Arthritis Foundation and the University Medical Center Utrecht. The training is based on the "Arthritis Self-Management Program" 1 but has recently gone through several updates, improvements and extensions 2 . The goal of the training is to improve self-management skills of patients and thereby improving their physical and emotional health and quality of life. Evaluations show that participants highly appreciate the training, but some of them have suggested that they would like to have an extra moment of training, (i.e., a booster session) after the ending of the regular program. Research shows that self-management programs are effective but mostly in the short term 3 . The effects of "Challenging Arthritis" may be enhanced and prolonged by organizing booster sessions. Objectives: Aim of this research is to make recommendations about organizing booster sessions based on 1) a literature search and 2) a needs assessment among former participants and peer trainers. Methods: A literature search was performed in databases like Google Scholar, PubMed and Science Direct, focusing on articles about the use of boosters in self-management interventions, limited to the years 2000–2016. Next to that, a needs assessment was conducted among participants and trainers on needs and preferences, using two separate online surveys. The survey for the participants, who followed a live training between 2012 and 2015, included items on the need for a booster and on preferences regarding its form, content and frequency. The survey for peer trainers addressed the perceived usefulness and the trainers' willingness to provide booster sessions. The resulting data were analyzed using SPSS and thematic analysis. Results: The literature search yielded 27 articles describing health interventions with aspects of self-management, including one or more booster sessions. From a theoretical perspective, boosters are a way to maintain new behavior over an extended period of time. As of yet, there is little evidence that the use of boosters lead to better outcomes in terms of health or health behavior, but it has been suggested that tailoring may lead to better results 4, 5 . Regarding the needs assessment, 124 participants and 34 trainers completed the survey. Results showed that almost half of the participants (47, 5%) expressed a need for a booster, while the other half (52, 5%) expressed little or no need. Participants who prefer a booster want to share experiences, learn how to stay active with self-management and how to cope with setbacks. Trainers think boosters are very useful for the participants to stay active with self-management and maintain behavior and they are unanimously willing to provide booster sessions. Conclusions: Boosters may contribute to the maintenance of newly acquired health behavior, although more research is needed on this subject. A substantial part of the participants expresses the need for a booster and trainers are highly motivated to provide it. Therefore, we think it's worthwhile to start experimenting with organizing booster sessions on a small scale and, depending on the outcomes, consider further implementation. References: References can be obtained from the first author. Disclosure of Interest: None declared